Regional diversification and labour market upgrading: Local access to skill-related high-income jobs helps workers escaping low-wage employment - Zoltán Elekes; Anna Baranowska-Rataj; Rikard Eriksson (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
This paper investigates how the evolution of local labour market structure enables or constrains workers as regards escaping low-wage jobs. Drawing on the network-based approach of evolutionary economic geography, we employ a detailed individual-level panel dataset to construct skill-relatedness networks for 72 functional labour market regions in Sweden. Subsequent fixed-effect panel regressions indicate that increasing density of skillrelated high-income jobs within a region is conducive to low-wage workers moving to betterpaid jobs, hence facilitating labour market upgrading through diversification. While metropolitan regions offer a premium for this relationship, it also holds for smaller regions, and across various worker characteristics.
Keywords: J21; J31; R11; R23; 330; skill-relatedness network; local labour market; low-wage workers; diversification and structural change; relatedness density